Fewer blue lakes and more murky lakes across the continental U.S.: Implications for planktonic food webs. (21st August 2018) - Leech, Dina M.; Pollard, Amina I.; Labou, Stephanie G.; Hampton, Stephanie E.
Abstract: Elevated allochthonous inputs of organic matter are increasingly recognized as a driver of ecosystem change in lakes, particularly when concurrent with eutrophication. Evaluation of lakes in a nutrient‐color paradigm (i.e., based on total phosphorus and true color) enables a more robust approach to research and management. To assess temporal and spatial patterns in nutrient‐color status for U.S. lakes and associated food web attributes, we analyzed the U.S. Environmental Protection Agency's National Lakes Assessment (NLA) data. With 1000+ lakes sampled in 2007 and 2012 in a stratified random sampling design, the NLA enables rigorous assessment of lake condition across the continental U.S. We demonstrate that many U.S. lakes are simultaneously experiencing eutrophication and brownification to produce an abundance of "murky" lakes. Overall, "blue" lakes decreased by 18% (46% of lakes in 2007 to 28% in 2012) while "murky" lakes increased by almost 12% (24% of lakes in 2007 to 35.4% in 2012). No statistical differences were observed in the proportions of "green" or "brown" lakes. Regionally, murky lakes significantly increased in the Northern Appalachian, Southern Plains, and Xeric ecoregions. Murky lakes exhibited the highest epilimnetic chlorophyll a concentrations, cyanobacterial densities, and microcystin concentrations. Total zooplankton biomass was also highest in murky lakes, primarily due to increased rotifer and copepod biomass. However, zooplankton : phytoplankton biomass ratios were low, suggesting reduced energy transfer to higher trophic levels. These results emphasize that many lakes in the U.S. are simultaneously "greening" and "browning", with potentially negative consequences for water quality and food web structure.